Evaluating a tobacco leaf humidification system involving nebulisation (2010)
A tobacco leaf humidifying system involving nebulisation was designned, implemented and evaluated; it had a system for monitoring and recording environmental conditions thereby producing an environment having more homogeneous relative humidity, ensuring better water use, better control of relative humidity and better control in managing cured tobacco leaf moisture content, thereby leading to a consequent improvement in final product quality. 55% to 75% relative humidity and 4 to 6 hour working ranges were obtained to en- sure leaf humidification reached 16% humidity on a wet basis. Two new designs are proposed for the conditioning stage regarding this conditioning chamber’s operational management, based on the results and field observations, which would allow better leaf management, thereby avoiding the risk of losses due to manipulation and over-humidification. This work strengthens research in the field of tobacco pos- tharvest technology, complementing other research projects which have been carried out in Colombia.